Customer Premises Equipment (CPE) Diagnostics Tool and Network Performance Analysis using Machine Learning - Wan Amirul Asyraf Mohd Hisham; Che Seman, Fauziahanim (Evolution in Electrical and Electronic Engineering, 2021)
In today’s era, DSL technology is growing rapidly which support high speed data transmission of a network between 2Hz to 20KHz as well as increase the fault rate. This project is mainly to determine the performance of the network based on the series data collection of different configuration setups of the CPE. Python programming is used to analyze the data measurement extracted from the GUI HG655m modem in VDSL2 network. The project is based on the equipment setup of real VDSL2 network in the lab consists of a network emulator, MSAN and CPE device. Ixia network emulator is used to emulate the real network condition for testing and measurement connected to MSAN and modem. The result of this project shows the relationship of the parameters which then are compared with the standard operation of the network to make observation of its performance. In the future, this project is recommended to perform artificial intelligence techniques using machine learning.